Biology and Treatment of Richter Transformation - Condoluci, Adalgisa; Rossi, Davide (Frontiers in Oncology, 2022)
Richter transformation (RT), defined as the development of an aggressive lymphoma on a background of chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL), represents a clinical unmet need because of its dismal prognosis. An increasing body of knowledge in the field of RT is arising from the recent development of preclinical models depicting the biology underlying this aggressive disease. Consistently, new therapeutic strategies based on a genetic rationale are exploring actionable pathogenic pathways to improve the outcome of patients. In this review, we summarize the current understandings on RT biology and the available treatment options.